Health care-seeking patterns for female genital mutilation/cutting among young Somalis in Norway - Mbanya, Vivian N. (BMC Public Health, 2018)
BACKGROUND: Female genital mutilation/cutting (FGM/C) is a great concern, considering all the potential health implications. Use of health care services related to FGM/C by women who have been subjected to FGM/C in Norway remains to be understood. This study aims to explore the health care-seeking patterns for FGM/C-related health care problems, among young Somalis in Norway. METHODS: A cross-sectional study involving 325 young Somalis in Oslo was conducted in 2014 using respondent-driven sampling (RDS) technique. The RDS was initiated by a small number of recruited seeds, who were given coded coupons to recruit their peers to participate in the study. Eligible recruiters who participated in the study and redeemed their coupons created the first wave of respondents. The first wave further recruited their peers, the second wave. The cycle continued to attain the needed samples. Using interviews and structured questionnaires, data on socio-demographic, FGM/C status and FGM/C-related use of health care were obtained. Logistic regressions were used to compute the odds ratio (OR) and the confidence interval (CI) for the associations between demographic variables, to circumcision status and health care-seeking for FGM/C. This study will focus on the 159 female participants of the total 325. RESULTS: While 51.6% of the 159 women were subjected to FGM/C, only 20.3% of them used health care services for FGM/C-related problems. Women’s FGM/C status was associated with age ≥ 12 years at migration, experience of stigma regarding FGM/C practice (p <  0.05), support of FGM/C practice, and place of birth of women (p <  0.05). CONCLUSION: Only one-fifth of the women with FGM/C sought care for FGM/C-related health problems. Our study does not provide the answers to why only a few of them sought care for FGM/C. However, as a large proportion of women did not seek care, it is important to investigate the reasons for this. For, we propose to conduct further research targeting girls and women who have undergone FGM/C to assess challenges in accessing health care services for proper intervention.